SEMIOTIC ANALYSIS OF THE LYRICS ON BTS’S ALBUM LOVE YOURSELF: ANSWER - Naomi Lastiarma Lumbantoruan; Rony Arahta Sembiring; Rosdiana Rajagukguk (Linguistik : Jurnal Bahasa dan Sastra, 2026)
This study aims to analyse the semiotic meanings in the lyrics of BTS songs from the album Love Yourself: Answer using Roland Barthes’ theory, which encompasses denotation, connotation and myth. This study employs a descriptive qualitative approach. The data consists of lyrics from five songs selected via purposive sampling based on their relevance to the themes of identity, emotion and self-love. Data collection was carried out through documentation using online lyric sources, whilst data analysis employed coding techniques based on Barthes’s semiotic framework. The results indicate that BTS’s lyrics contain layered meanings that reflect emotional experiences as well as the construction of the ideology of self-love as a form of healing and resistance against social pressure.